2020
DOI: 10.1021/acsomega.0c02968
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Mechanism of 1,3,5,7-Tetranitro-1,3,5,7-tetrazocane Accelerated by Nano-Aluminum Hydride (AlH3): ReaxFF-Lg Molecular Dynamics Simulation

Abstract: ReaxFF-low-gradient reactive force field with CHONAl parameters is used to simulate thermal decomposition of 1,3,5,7-tetranitro-1,3,5,7-tetrazocane (HMX) and AlH 3 composite. Perfect AlH 3 and surface-passivated AlH 3 particles were constructed to mix with HMX. The simulation results indicate HMX is adsorbed on the surface of particles to form O–Al and N–Al bonds. The decomposition of HMX and AlH 3 composite is an exoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Meanwhile, it is found that the initial reaction path of HMX nanocrystals at low temperature is the breaking of the C-H bond, and the product at low temperature is the same as that at high temperature. Zhao et al 98 studied the pyrolysis process of nano-AlH 3 and HMX composites. The results show that HMX adsorbs on the particle surface by forming Al-O and Al-N bonds.…”
Section: Pyrolysis and Combustion Mechanism Of Hmxmentioning
confidence: 99%
“…Meanwhile, it is found that the initial reaction path of HMX nanocrystals at low temperature is the breaking of the C-H bond, and the product at low temperature is the same as that at high temperature. Zhao et al 98 studied the pyrolysis process of nano-AlH 3 and HMX composites. The results show that HMX adsorbs on the particle surface by forming Al-O and Al-N bonds.…”
Section: Pyrolysis and Combustion Mechanism Of Hmxmentioning
confidence: 99%
“…Relatively few studies on decay details of FOX-7, concerning the coupling effect of heat stimulation and low-velocity impact, have been published yet. ReaxFF molecular dynamics simulations (RMD) have been shown to reveal the decomposition mechanism of energetic materials [ 27 , 28 , 29 ]. Herein, the RMD is employed to investigate the effect of heat coupled with compression in different directions on the decomposition reaction network, the final products, and the reaction kinetic parameters of the FOX-7 decomposition.…”
Section: Introductionmentioning
confidence: 99%